Clinical manifestations but not cytokine profiles differentiate adult-onset Still’s disease and sepsis - Rau, Monika Christine; Schiller, Martin; Krienke, Stefan; Heyder, Petra; Lorenz, Hanns-Martin; Blank, Norbert (The journal of rheumatology, 2010)
Objective. To analyze clinical manifestations, serum ferritin, and serum cytokine levels in patients with adult-onset Still’s disease (AOSD) or bacterial sepsis and to evaluate their potential use for differential diagnosis. - Methods. Twenty-two consecutive patients with the first flare of AOSD and 6 patients with an established diagnosis of AOSD under immunosuppressive therapy were compared with 14 patients with bacterial sepsis. Clinical manifestations were scored in a Pouchot AOSD activity score including elevated serum ferritin levels to obtain a modified Pouchot score. Serum cytokine profiles were analyzed from each patient. - Results. The scores of clinical manifestations using a modified Pouchot activity score were significantly higher in patients with active untreated AOSD (mean 5.60 ± 1.93) compared with patients with chronic AOSD (mean 1.16 ± 0.98; p < 0.001) and patients with sepsis (mean 2.38 ± 1.19; p < 0.001). A modified Pouchot score ≥ 4 shows a sensitivity of 92% and a specificity of 93% for active AOSD. Serum cytokine levels of interleukin 1ß (IL-1ß), IL-6, IL-8, IL-10, IL-12, IL-18, interferon-γ, tumor necrosis factor-α, and calprotectin were elevated in acute AOSD and sepsis. Significant differences were detected only in patients with sepsis who had higher levels of IL-6 and IL-8. The overlap of the 2 groups limits the use of cytokines for differential diagnosis in individual patients. - Conclusion. A modified Pouchot AOSD activity score including elevated serum ferritin levels was more useful to confirm the diagnosis of AOSD compared to patients with sepsis. Elevated serum cytokines correlate with inflammation but are of limited use to differentiate between active AOSD and bacterial sepsis.
Gesehen am 10.05.2023